Pengaruh Kepemilikan Institusional Terhadap Relevansi Nilai Informasi Hierarki Nilai Wajar - Desni Ramadhani; Nurzi Sebrina (Universitas Negeri Padang, 2020)
The purpose of this research is to examine the relevance of fair value hierarchy information and the effect of institutional ownership on the relevance of fair value hierarchy information. This research is a causal associative research with a quantitative approach. Research conducted on banking companies listed on the Indonesian Stock Exchange period 2015-2018, which were determined by purposive sampling method so that 37 companies were selected as samples. The hypotheses were tests using multiple regression. The results indicate that the fair value level 2 is more relevant than the level 1 and 3, this research proves that the fair value level 2 is relevant for decision making of investor. In subsequent tests, institutional ownership does not have a positive effect on the relevance of fair value level 1, level 2 and level 3.